Improve TAT Refurbishment Process Excavator 20 Tons in Heavy Equiment Workshop - Refnal Marzuki; Rino Sukma; Nofriyandi R; Rusmardi Rusmardi (METAL: Jurnal Sistem Mekanik dan Termal, 2022)
This study discusses the turnaround time (TAT) process in the 20 Tons Excavator refurbishment process carried out by a heavy equipment repair shop in Palembang City. TAT is the time range for the completion of the work, starting from when the tool arrives at the workshop until the job is completed. In this study, the employer is the owner of the heavy equipment, and the work recipient is the workshop where the heavy equipment is carried out. Based on the workshop records, during the 20 Tons TAT Excavator's refurbishment process, the best time was achieved was 56 working days. At the same time, the entrepreneur felt that 56 days was too long and the entrepreneur asked that this repair could be completed within a maximum of 30 working days. This delay causes huge losses for entrepreneurs resulting in lost business opportunities. This research aims to increase the TAT for the completion of the 20 Tons Excavator refurbishment work completion time following the work completion agreement. For this reason, it is necessary to conduct a study to determine the causes of delays in repair work. In this study, the authors use the method used in this analysis: Define, Measure, Analyze, Improve and Control (DMAIC). Based on the research, it was found that three things significantly affect the delay in completing the work, namely the limited area for painting, work agreements as a result of the availability of spare parts and completion of work from third parties. In the process of reconditioning heavy equipment, namely setting up the painting area, availability of spare parts and ensuring the completion of work submitted to third parties, to achieve the fastest time for completion of work